PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO TUTORIAL FRENCH MANICURE UNTUK KELAS X TATA KECANTIKAN KULIT DAN RAMBUT DI SMKN 1 SOOKO MOJOKERTO - Sherlynda Devtiana; Sri Dwiyanti; Sri Usodoningtyas; Dindy Sinta Megasari (Jurnal Tata Rias, 2024)
Nail art is a form of beauty nail art that is increasingly in demand among society, especially among teenagers. Nail art skills not only provide aesthetic value, but also open up career opportunities in the beauty industry. This research aims to develop learning media for French manicure video tutorials on learning outcomes for hand care and nail coloring in the basics of beauty subjects and to determine the validity of the video media. This research method uses the 4D R&D model (Define, Design, Develop, Disseminate). The subjects in this research were 33 class x beauty and beauty students at SMKN 1 Sooko. Data collection techniques were carried out through observation, interviews and questionnaires. The research method used is the R&D (Research&Development) development method with the 4D development model. The R&D (Research and Development) method is a research method that builds new product media or improves existing product media and tests product effectiveness, Sugiyono (2019). The 4D (Four D) development model is a learning device development model. This model was developed by S. Thiagarajan, Dorothy S. Semmel, and Melvyn I Semmel. The 4D development model consists of four development stages, namely: Define, Design, Development and Disseminate. The results of the research are as follows: 1) Stages of the process of developing video learning media, video tutorials that have been developed through expert validation tests and trials on student responses to get the criteria "Very Good. 2) Validation of media suitability obtained expert validation results with an average of 90% for the material aspect, 94.4% for the media aspect, and 89.4% for the language aspect, while the average result for each aspect was 90.8%. So it can be categorized as "Very Good / Very Appropriate" for use during the learning process. Keywords: Learning Media, Video Tutorial, Nail art, French Manicure